1940
DOI: 10.1084/jem.72.6.747
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Studies of Prostatic Secretion

Abstract: Benign enlargement of the prostate, a lesion wherein localized overgrowth of an organ develops in old age, occurs in senile dogs and in no other species commonly used in the laboratory (1, 2). The high incidence of this spontaneous disease facilitated the present investigation of a condition which often involves the prostate gland of old men.No quantitative experimental studies of prostatic enlargement in the dog have been reported previously. The production of shrinkage of the hypertrophied gland was studied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
66
0
1

Year Published

1941
1941
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 333 publications
(69 citation statements)
references
References 23 publications
2
66
0
1
Order By: Relevance
“…Around this time, Charles Huggins (FIG. 1a) established a method to measure the effect of various hormonal manipulations on prostatic function 12 . He found that castration or oestrogen administration resulted in glandular atrophy, which could be reversed by readministration of androgen.…”
Section: Box 1 Androgen Production and Actionmentioning
confidence: 99%
“…Around this time, Charles Huggins (FIG. 1a) established a method to measure the effect of various hormonal manipulations on prostatic function 12 . He found that castration or oestrogen administration resulted in glandular atrophy, which could be reversed by readministration of androgen.…”
Section: Box 1 Androgen Production and Actionmentioning
confidence: 99%
“…Prostate cancer can often be cured with definitive local intervention (surgery or radiation), but once the cancer metastasizes, it is incurable. Our most effective regimens for treating metastatic prostate cancer have arisen from the pioneering experiments, in which suppression of testicular testosterone production was shown to cause tumor regression (Huggins & Clark 1940). Since then, our ability to inhibit androgen synthesis and androgen receptor (AR) signaling has improved, and several agents are now approved for treatment of metastatic prostate cancer (Friedlander & Ryan 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the lack of knowledge regarding several aspects of BPH pathogenesis, its well recognized that the development of the histological features of the disease is dependent on the bioavailability of TT and its metabolite, dihydrotestosterone (18). A congenital lack of 5α-reductase results in a vestigial prostate gland (19) and castration in a man leads to glandular atrophy and regression of LUTS (20). It's also reasonable to think that systemic effects of TT in bone and muscle mass, fat mass, body energy, and physical, sexual, and cognitive function may also be reflected on LUTS.…”
Section: Discussionmentioning
confidence: 99%